PENGARUH REKRUTMEN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR ARTHA DAYA - Budiwinarto, Kim (Widya Dharma Journal of Business - WIJoB, 2024)
The purpose of this study was to determine the effect of recruitment, motivation and work environment on employee performance of PT. BPR Artha Daya. The population of this research is the employees of PT. BPR Artha Daya totaling 52 people and all of them were used as research samples This research is a quantitative assessment of the data collection method used in this study using a questionnaire by giving a set of questions or written questions to the respondent to answer. The analysis technique used is multiple linear regression model, t-test, F-test, and the coefficient of determination. The results of the analysis show that there are recruitment has a significant effect on the performance of employees of PT. BPR Artha Daya, motivation has a significant effect on the performance of employees of PT. BPR Artha Daya., and the work environment has a significant effect on the performance of employees of PT. BPR Artha Daya.